Neuroprotective effects of Glochidion zeylanicum leaf extract against H2O2/glutamate-induced toxicity in cultured neuronal cells and Aβ-induced toxicity in Caenorhabditis elegans - Duangjan, Chatrawee; Rangsinth, Panthakarn; Zhang, Shaoxiong; Gu, Xiaojie; Wink, Michael; Tencomnao, Tewin (Biology, 2021)
Oxidative stress plays a crucial role in the development of age-related neurodegenerative diseases. Previously, Glochidion zeylanicum methanol (GZM) extract has been reported to have antioxidant and anti-aging properties. However, the effect of GZM on neuroprotection has not been reported yet; furthermore, the mechanism involved in its antioxidant properties remains unresolved. The study is aimed to demonstrate the neuroprotective properties of GZM extract and their underlying mechanisms in cultured neuronal (HT-22 and Neuro-2a) cells and Caenorhabditis elegans models. GZM extract exhibited protective effects against glutamate/H2O2-induced toxicity in cultured neuronal cells by suppressing the intracellular reactive oxygen species (ROS) generation and enhancing the expression of endogenous antioxidant enzymes (SODs, GPx, and GSTs). GZM extract also triggered the expression of SIRT1 /Nrf2 proteins and mRNA transcription of antioxidant genes (NQO1, GCLM, and EAAT3) which are the master regulators of cellular defense against oxidative stress. Additionally, GZM extract exhibited protective effects to counteract beta-amyloid (A beta)-induced toxicity in C. elegans and promoted neuritogenesis properties in Neuro-2a cells. Our observations suggest that GZM leaf extract has interesting neuritogenesis and neuroprotective potential and can possibly act as potential contender for the treatment of oxidative stress-induced Alzheimer's disease (AD) and related neurodegenerative conditions; however, this needs to be studied further in other in vivo systems.
Im Titel ist die Zahl 2 jeweils tiefgestellt
Gesehen am 24.11.2021